Improving the Fifth-Grade Elementary Students’ Learning Activity, Learning Outcome, Motivation, and Critical Thinking Skills Using the PROSOTAN HORAY Model - Siti Fatimah; Dessy Dwitalia Sari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The research problem in this paper comes from students' low activity, motivation, critical thinking skills, and learning outcomes. This paper describes the improvement of learning quality through educator activities, students’ learning outcomes, students’ learning activity analysis, motivation, and students’ critical thinking skills. The research usesClassroom Action Research (PTK), which was conducted in 4 meetings. The research subjects were 23 fifth-grade elementary students. The types of research data were qualitative and quantitative data. Qualitative data were obtained from observation of educators’ activities, questionnaires on learning motivation, students’ learning activities, and students’ critical thinking skills. Quantitative data are obtained through individual written tests. The benchmarkfor research success indicates that the value is ≥ 82% or ≥ 75. Based on the research data findings and results, it can be concluded that teaching and learning activities by applying the PROSOTAN HORAY are able to provide an increase in motivation, activity, critical thinking skills, and learning outcomes for students.